Survey Research About the Importance of English for Young Learners at Elementary Schools - Ayu Oktaviani; Putra Saparingga; Dwi Susanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The objective of the research was to find out teachers’ perceptions about the importance of English for young learners at Elementary Schools in Lubuklinggau.Type of survey used in this study was cross-sectional survey research. To select the sample, cluster random sampling used in this research. Cluster random sampling here focused on the eight (8) districts of Lubuklinggaucity (Lubuklinggau Utara1-2, Selatan1-2, Barat1-2 and Timur1-2). The researchers chose randomly four (4) districts.The researcher used the representative sample from each districts chosen. 100 teachers, 100 students, and 100 parents are samples. The researcher used survey research and the data were collected by using questionnaire and interview. Technique for analyzing the data used simple basic statistical technique. The data are scored by using Likert scale. The results of the research were: 1) the respondents agree that the children who learn foreign language early as possible will get the better result. 2) the respondents very agree that economic globalization has pushed the necessity of workers who are able to speak English. 3) the respondents agree that the enthusiasm of parents in supporting their children to learn English hopefully can help their children will have social and economic benefits in the future. Based on the result of the data, it can be concluded that the teachers, students and parents of Elementary Schools in Lubuklinggau agree that English for Young Learners is important. Keyword: survey, english for young learner, elementary schools